Edutainment Radio Programmes on HIV AIDS as a Strategy to Encourage Behavioural Change among the Youth in Nyanza Province - Kenya - Mboya, Rosemary Alakie (Daystar University, 2005)
The purpose of this study was to identify, analyze and evaluate the effectiveness of Edutainment Radio Programmes on HIV AIDS as a strategy to encourage behavioural change among the youth in Nyanza. The study sought to determine whether youth actually listened to HIV AIDS programmes and assessed how the programmes impacted on the youth and whether or not the programmes are edutainment in nature. A random sampling technique was used to select 200 secondary school students to whom the questionnaires were administered. A semi- structured telephone interview was carried out with three radio producer presenters whose broadcast stations were identified by respondents as the most listened to. The key findings of this study indicated that the youth in the selected area of study were relatively aware of HIV AIDS, and that 95.4% of the youth listened to radio, and 78% listened to radio programmes on HIV AIDS. The findings indicate that as a strategy, edutainment radio programmes on HIV AIDS can be effective, informative and their appeal to the youth could encourage the behavioural changes needed in our society as a preventive measure against HIV AIDS.
Master's Thesis
Keywords: Edutainment Radio Programmes